Plate versus intramedullary nail fixation in the treatment of distal tibial fractures: Clinical and functional impacts on the ankle - Coelho, Henrique Calvelli; Nazzaro, André da Cruz Barbosa; Chen, Daniel Shing Yi; Pinto, Guilherme Arcoverde (Journal of the Foot & Ankle, 2026)
Objective: To compare the effectiveness of plate and intramedullary nail fixation in the treatment of distal tibial fractures and evaluate the impact of each technique on ankle function. Methods: An integrative literature review was conducted, including articles published between 2010 and 2025 in the PubMed, Scopus, Web of Science, LILACS, and SciELO databases, which compared the two surgical methods and presented relevant clinical and functional data. Initially, 512 studies were identified through a systematic search. After applying the inclusion and exclusion criteria, 20 articles were included in the final sample for analysis. Results: The analysis revealed that both techniques have high consolidation rates, ranging from 92% to 97%, with plate fixation associated with greater anatomical precision in complex intra-articular fractures and intramedullary nail fixation associated with shorter surgical time, less soft-tissue trauma, and earlier rehabilitation. Postoperative complications differ by method: plate fixation is most often associated with surgical site infection and delayed soft-tissue healing, while intramedullary nail fixation is at higher risk of mechanical misalignment and anterior knee pain. Regarding ankle function, evaluated mainly by standardized clinical scores such as the American Orthopaedic Foot and Ankle Society, quality of life indexes (SF-36), and range of motion measurements, the results showed equivalence between the techniques in extra-articular fractures. However, a slight functional superiority of plate fixation in complex joint fractures was observed, attributed to its greater capacity to anatomically restore the distal tibial articular surface. Conclusion: The research demonstrates that there is no absolute superiority of one method over the other, and the choice depends on the fracture pattern and the patient’s clinical profile. The findings reinforce the importance of individualizing treatment, preventing complications, and optimizing joint function, and highlight the need for prospective studies with prolonged follow-up and standardized assessment instruments. Level of Evidence I; Systematic Review.